Pilihan Rasional Kiai dan Desain Pendidikan Toleransi di Pondok Pesantren Tebuireng dan Nurul Jadid - Mursyid Mursyid (Islamica: Jurnal Studi Keislaman, 2016)
This article discusses the role of kyai and the learning design used in educating tolerance in two pesantrens, namely Pesantren Tebuireng of Jombang and Pesantren Nurul Jadid Probolinggo. The two pesantrens educate their students to internalize and actualize tolerant value and attitude. However, the value of tolerance is not taught formally like other subjects, but rather developed through informal learning and examplary model by the kyais in both pesantrens. As the kyais in both pesantrens have inclusive views and tolerant attitudes in the context of pluralistic society, the students learn from their tolerant views and attitudes, and adopt this value in their daily activities. Using Colemanâ€™s rational choice theory, it can be argued that the kyais of both pesantrens have consciously adopted the value of tolerance as one of the important instructional values. Therefore, it can be concluded that pesantren is the place of seeding the values of tolerance, while the learning design used by pesantrens can be called â€œtolerance exhibition modelâ€.